Optimization of the criminal legal system: A reconstruction of additional sentences as substitute for replacement money for corruption in Indonesia - Malo, Henderina; Hartiwiningsih, Hartiwiningsih; Sulistyanta, Sulistyanta (Edelweiss Applied Science and Technology, 2025)
This is a normative study with the main objective of reconstructing the regulation of prison sentences as an additional penalty in the Eradication of Crime of Corruption Act (ECCA). It focused on achieving objective law through certainty, justice, and expediency. The findings of the study identify several problems related to the regulations in prison sentences as a replacement for additional sentences. For the payment of replacement money, a fine is neither normative nor practical. This nonconformity with the objectives of law, including certainty, justice, and expediency, highlights the necessity for the reconstruction of existing regulations. The reconstruction approach involves a comprehensive analysis of various aspects of existing problems in regulations and their implementation in prison sentences as a substitute for the additional penalty of replacement money. As a result, some additional regulations are proposed to overcome the obscurity of prison sentences as a substitute for the additional penalty of unpaid replacement money as regulated in the ECCA that prevails at this moment.